BLNK mutation associated with T-cell LGL leukemia and autoimmune diseases: Case report in hematology - Fouquet, Guillemette; Rossignol, Julien; Ricard, Laure; Guillem, Flavia; Couronné, Lucile; Asnafi, Vahid; Vavasseur, Manon; Parisot, Mélanie; Garcelon, Nicolas; Rieux-Laucat, Frédéric; Mekinian, Arsène; Hermine, Olivier (Frontiers in Medicine, 2022)
We present the case of a female patient with a heterozygous somatic BLNK mutation, a T-cell LGL (large granular lymphocyte) leukemia, and multiple autoimmune diseases. Even though this mutation seems uncommon especially in this kind of clinical observation, it could represent a new mechanism for autoimmune diseases associated with LGL leukemia. The patient developed several autoimmune diseases: pure red blood cell apalsia, thyroiditis, oophoritis and alopecia areata. She also presented a T-cell LGL leukemia which required treatment with corticosteroids and cyclophosphamide, with good efficacy. Interestingly, she had no notable infectious history. The erythroblastopenia also resolved, the alopecia evolves by flare-ups, and the patient is still under hormonal supplementation for thyroiditis and oophoritis. We wanted to try to understand the unusual clinical picture presented by this patient. We therefore performed whole genome sequencing, identifying a heterozygous somatic BLNK mutation. Her total gamma globulin level was slightly decreased. Regarding the lymphocyte subpopulations, she presented a B-cell deficiency with increased autoreactive B-cells and a CD4+ and Treg deficiency. This B-cell deficiency persisted after complete remission of erythroblastopenia and LGL leukemia. We propose that the persistent B-cell deficiency linked to the BLNK mutation can explain her clinical phenotype. We believe that BLNK could be a new gene of interest in autoimmune diseases, which could warrant further explorations and may lead to a better understanding of these pathologies.